Rancangan Cognitive-Behavioral Therapy (CBT) Untuk Anak Yang Mengalami Attention Deficit Hyperactivity Disorder (ADHD) Dengan Komorbid Oppositional Defiant Disorder (ODD) Di Bandung - Hedi Wahyudi (SCHEMA (Journal of Psychological Research), 2011)
The aim of this study was to make a design of Cognitive Behavioral Therapy (CBT) with a focus on Attention Deficit and Hiperactivity children with Oppositional Defiant Disorder (ODD) as a comorbid to increase childrens educational skills in managing aggressive and oppositional behavior with support from parents and environment.  For this purpose 3 children with a diagnosisi of ADHD combined type participated in the study. Core symptoms of ADHD and Oppositional Defiant Disorder (ODD) individual problem behavior were assessed by parent and teacher from questionnaires, interviewed and observed each child. The results of a case study indicate that the 3 children with ADHD and ODD showed the lack of emphaty, negative self-esteem and self concept, so they can’t regulate their self to act in social interaction. They don’t understand how to generated rules that the therapies and parents taught them in other situations eventhough they are more attentive, less hyperactive, and more thinkfull before act. To make them more adaptive in social life, they need to change their way to think about their self, their schemata, and they must have base skills to socialize. This can do through counseling to give insight and modeling behavior problem solving. We conclude that CBT may be a promising component in the treatment of ADHD providev that aspects of generalization are considered during the traetment that reduce problems of self-guidance.